Discovery and identification of EIF2AK2 as a direct key target of berberine for anti-inflammatory effects - Wei Wei; Qingxuan Zeng; Yan Wang; Xixi Guo; Tianyun Fan; Yinghong Li; Hongbin Deng; Liping Zhao; Xintong Zhang; Yonghua Liu; Yulong Shi; Jingyang Zhu; et al. (2022)
Using chemoproteomic techniques, we first identified EIF2AK2, eEF1A1, PRDX3 and VPS4B as direct targets of berberine (BBR) for its synergistically anti-inflammatory effects. Of them, BBR has the strongest affinity with EIF2AK2 via two ionic bonds, and regulates several key inflammatory pathways through EIF2AK2, indicating the dominant role of EIF2AK2. Also, BBR could subtly inhibit the dimerization of EIF2AK2, rather than its enzyme activity, to selectively modulate its downstream pathways including JNK, NF-κB, AKT and NLRP3, with an advantage of good safety profile. In EIF2AK2 gene knockdown mice, the inhibitory IL-1β, IL-6, IL-18 and TNF-α secretion of BBR was obviously attenuated, confirming an EIF2AK2-dependent anti-inflammatory efficacy. The results highlight the BBR's network mechanism on anti-inflammatory effects in which EIF2AK2 is a key target, and inhibition of EIF2AK2 dimerization has a potential to be a therapeutic strategy against inflammation-related disorders.